Do Environmental Performance and Corporate Social Responsibility Enhance Firm Value? The Moderating Role of Independent Commissioners in Indonesian Mining Companies - Ariya Antrika; Rulyanti Susi Wardhani; Nur Ahmad Ricky Rudianto (Goodwood Publishing, 2026)
Purpose: This study aims to examine the effects of environmental performance and corporate social responsibility on firm value, as well as to investigate whether independent commissioners moderate these relationships in Indonesian mining companies. Methodology: This study employs a quantitative approach using secondary data from annual reports, sustainability reports, and financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sample comprises 20 companies selected through purposive sampling. Results: Environmental performance has no significant effect on firm value, whereas corporate social responsibility has a negative and significant effect. Independent commissioners do not moderate the environmental performance firm value relationship but mitigate the negative effect of corporate social responsibility on firm value. Conclusions: Corporate social responsibility significantly influences firm value, while environmental performance does not. Independent commissioners mitigate Corporate Social Responsibility (CSR) negative effect on firm value but do not moderate the environmental performance firm value relationship. Limitations: This study is limited to Indonesian mining companies during the 2022–2024 period. Contributions: This study contributes to the sustainability and corporate governance literature by providing empirical evidence from the Indonesian mining sector.